2012
DOI: 10.3109/08923973.2012.654610
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative description of the peptide sharing between poliovirus andHomo sapiens

Abstract: In a companion paper, we reported that pentapeptides from human poliovirus 1, Mahoney strain, occur repeatedly in human proteins for a total of more than 18,000 overlaps. In the present study, we describe the distribution of the polio pentapeptides throughout biochemical pathways and networks characterizing functions and tissues in the human host. The present study might be of help to better define the poliovirus-host relationships as well as for designing peptide modules with anti-polio activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…In conclusion, the present study confirmed and extended previous reports from this laboratory and others presenting evidence for a massive peptide overlap between viral and human proteomes. Having as a reference frame such a corpus of data, here we detailed the peptide commonality between WNV and the human proteome.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, the present study confirmed and extended previous reports from this laboratory and others presenting evidence for a massive peptide overlap between viral and human proteomes. Having as a reference frame such a corpus of data, here we detailed the peptide commonality between WNV and the human proteome.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon concerns all human proteins. For example, there are 18 000 pentapeptide overlaps between the poliovirus and the human proteome (Capone et al ., ), while a single immunogenic pentapeptide (VGGVV) within beta‐amyloid is shared by HSV‐1 and 68 other viruses (Carter, ). Host/pathogen interactomes likely result from this homology, which enables pathogen proteins to mimic their human counterparts and compete with their usual binding partners.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon concerns all human proteins. For example, there are 18 000 pentapeptide overlaps between the poliovirus and the human proteome (Capone et al, 2012), while a single immunogenic pentapeptide (VGGVV) within beta-amyloid is shared by HSV-1 and 68 other viruses (Carter, 2010b).…”
Section: Pathogen-derived Autoimmunitymentioning
confidence: 99%
“…This problem is extensive and concerns all human proteins, along their entire length. For example, there are 18,000 pentapeptide overlaps between the poliovirus and the human proteome [181] while a single immunogenic pentapeptide (VGGVV) within the beta-amyloid peptide is identical to that within proteins from the herpes simplex virus and from 68 other viral species [19]. The extensive host/pathogen interactomes of numerous viruses, bacteria, and parasites no doubt result from this homology which enables pathogen proteins to mimic particular motifs within their human counterparts and to compete for their usual binding partners.…”
Section: Discussionmentioning
confidence: 99%